On Experimental Research in Oligopoly - Friedman, J. W. (Review of Economic Studies, 1969)
Journal Article On Experimental Research in Oligopoly Get access J. W. Friedman J. W. Friedman University of Rochester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 4, October 1969, Pages 399–415, https://doi.org/10.2307/2296467 Published: 01 October 1969 Article history Received: 04 August 1968 Revision received: 25 October 1968 Published: 01 October 1969